2023
DOI: 10.3389/fimmu.2023.1165602
|View full text |Cite
|
Sign up to set email alerts
|

Loss of NLRP3 reduces oxidative stress and polarizes intratumor macrophages to attenuate immune attack on endometrial cancer

Abstract: IntroductionThe interaction between endometrial cancer (EMC) cells and intratumoral macrophages plays a significant role in the development of the disease. PYD domains-containing protein 3 (NLRP3) inflammasome formation triggers caspase-1/IL-1β signaling pathways and produces reactive oxygen species (ROS) in macrophages. However, the role of NLRP3-regulated ROS production in macrophage polarization and the subsequent growth and metastasis of EMC remains unknown.MethodsWe conducted bioinformatic analysis to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…32 The reduction of oxidative stress and polarization of intratumor macrophages is linked to NLRP3 loss in alleviating endometrial cancer. 33 MiR-22 is able to restrain cell viability of ovarian cancer cells, which is mediated by NLRP3 and PI3K/AKT signaling pathway. 34 Nigericin or in combination with LPS exert a suppressive role in the cell viability and proliferation of breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…32 The reduction of oxidative stress and polarization of intratumor macrophages is linked to NLRP3 loss in alleviating endometrial cancer. 33 MiR-22 is able to restrain cell viability of ovarian cancer cells, which is mediated by NLRP3 and PI3K/AKT signaling pathway. 34 Nigericin or in combination with LPS exert a suppressive role in the cell viability and proliferation of breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, polarization of TAMs to the M1 phenotype can inhibit tumor growth [ 37 ]. Previous studies have demonstrated a negative correlation between infiltration of M2-like TAMs and the prognosis of EC [ 38 40 ]. Our findings indicate that the ICD-high group exhibited higher infiltration of M2 macrophages compared to the ICD-low group, with a positive correlation between risk score and M2 macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the NOD-like receptors have been identified as crucial factors in tumorigenesis, angiogenesis, cancer stemness, and chemoresistance. In endometrial cancer (EMC), dysregulation of the NOD-like receptor family protein (NLRP) has been shown to impair the phagocytic function of macrophages and reduce the CD + T cell population, thereby promoting the growth, invasion, and metastasis of EMC cells (Zhu et al, 2023). Furthermore, recent research has revealed that tumor cells can utilize lipids secreted by adipocytes to promote tumor progression and chemoresistance through metabolic reprogramming.…”
Section: Discussionmentioning
confidence: 99%